2016
DOI: 10.1016/j.molonc.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

VCP inhibitors induce endoplasmic reticulum stress, cause cell cycle arrest, trigger caspase‐mediated cell death and synergistically kill ovarian cancer cells in combination with Salubrinal

Abstract: Abbreviations: AAA-ATPase, ATPase associated with diverse cellular activities; BRCA1/2, breast cancer 1/2; PARP1, poly ADP-ribose polymerase-1; DBeQ, N 2 ,N 4 -dibenzylquinazoline-2,4-diamine; PBS, phosphate buffered saline; EGF, epidermal growth factor; TBS, tris-buffered saline; PERK, protein kinase R-like endoplasmic reticulum kinase; TCGA, the Cancer Genome Atlas; PVDF, polyvinylidene difluoride; IRE1a, inositol-requiring enzyme 1 alpha; CHOP, CCAAT/enhancer-binding protein homologous protein; ATF4, activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
77
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 60 publications
4
77
0
Order By: Relevance
“…Bastola et al described the preclinical activity of VCP inhibitors in ovarian cancer cells, and final outcomes showed that VCP inhibitors were able to induce ER stress, cause cell cycle arrest, and trigger caspase‐mediated cell death. Thus, VCP inhibitor can be used as a single agent or combined with other antitumor compounds …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bastola et al described the preclinical activity of VCP inhibitors in ovarian cancer cells, and final outcomes showed that VCP inhibitors were able to induce ER stress, cause cell cycle arrest, and trigger caspase‐mediated cell death. Thus, VCP inhibitor can be used as a single agent or combined with other antitumor compounds …”
Section: Discussionmentioning
confidence: 99%
“…Among these specific inhibitors, NMS‐873 was initially developed as an allosteric, non‐ATP‐competitive, and potent noncovalent VCP inhibitor that impairs the ERAD pathway, activates the unfolded protein response (UPR), and induces apoptosis . In addition, other findings have revealed VCP as a potential target and inhibiting VCP has been associated with improved antitumor activity in vitro and in vivo . To date, the role of VCP in enhancing tumor radiation sensitivity has not been characterized in ESCC cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Among the altered proteins, valosin‐containing protein (VCP) is a member of the AAA ATPases was identified as overexpressed protein which formed a central node in protein network analysis. Elevated VCP expression show positive correlation with progression, metastatic potential of Non‐small cell lung cancer (NSCLC), Ovarian, Colorectal cancer, and Osteosarcoma (Bastola, Neums, Schoenen, & Chien, ; Fu et al, ; Long, Zhang, Liu, Huang, & Luo, ; Valle et al, ). Furthermore, it has been reported that elevated VCP expression would lead to the poor prognosis of PCa (Tsujimoto et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ER stress marker levels were increased in Bap31 knockout mice after tunicamycin injection compared with those in control mice [35]. The depletion of VCP by siRNA induces ER stress and the unfolded protein response (UPR) [36]. In addition, the C-terminus of Bap31 can be cleaved by caspase 8 to generate p20, which participates in apoptosis.…”
Section: Discussionmentioning
confidence: 99%